Current Role and Importance of USG Guided FNAC for Rapid Diagnosis of Suspicious Mass Lesions - Maulik Jethva; Parth Dholakiya; Hiral Hapani (Asian Journal of Medical Radiological Research, 2020)
Background: Ultrasound guided Fine needle aspiration is a diagnostic procedure that inserts a small needle into a suspicious mass to extract some cells which are then visualized under the microscope. The aim of the present study was to determine utility and safety of ultrasound guided FNAC in rapid evaluation of various mass lesions. Subjects and Methods: In this study, 120 patients of age between 20-60 years with various mass lesions referred for ultrasonography guided FNAC to the department of radiodiagnosis, PDU Medical College and Civil hospital, Rajkot, Gujarat over a period of 1.5 years from 1/5/2018 to 1/11/2019are included. Results: Ultrasonography guided FNAC was performed by the same investigator, an experienced radiologist, using a real time scanner (logicP9; GE Healthcare) under standard septic precautions. Conclusion: Our study contributes to the conclusion that USG guided FNAC can easilybe used for the aspiration of lesion of the breast, thyroid, lymph nodes, liver, lung, musculoskeletal system etc. It does not use ionizing radiation, has no known harmful effects, and provides rapid diagnosis of the suspicious mass lesions &a firm diagnosis of impalpable lesions can be made preoperatively. Advantages of USG guided FNAC:- 1. Cost effectiveness, 2. No radiation hazards, 3. Easy to perform, 4. Dynamic evaluation of vessels, 5. Perfect real time Localization of the target lesion,